Effectiveness of clinical and instrumental follow-up for cutaneous melanoma. (September 2022) - Toia, Francesca; Cajozzo, Marta; Rosatti, Fernando; Di Lorenzo, Sara; Rinaldi, Gaetana; Mazzucco, Walter; Cordova, Adriana
Abstract: Introduction: Follow-up guidelines for melanoma greatly differ in the methods of screening for recurrence, and timing and duration of the follow up, with many areas of controversy and a lack of general consensus. The aims of this study are to present our protocol and case series for follow up and to summarize and discuss current literature on melanoma follow-up guidelines/recommendations in different countries. Methods: We retrospectively reviewed 539 patients operated for melanoma between 2004 and 2013 at the same Institution. Data on the diagnostic role of the different clinical and instrumental detection methods were adjusted for sex, age at diagnosis, staging and evaluated by Fisher's exact test and multivariate analysis. Recommendations from the literature were summarized and discussed. Results: Local recurrences and second melanoma were always identified through physical examination, irrespectively of melanoma staging. Regional metastases were most often identified through physical examination and ultrasound, being more frequent in stage II and III, while distant metastases were most often identified through CT scans. Surveillance follow-up schedules vary significantly depending on country, physician specialty, and stage of disease, with a lack of evidence on the efficacy of the different schemes. Similarities and controversies in the different follow-up protocols are presented and discussed. Conclusion: Our clinical series showed that physical examination is very powerful in identifying local recurrences and second melanomas. Physical examination and ultrasound are equally powerful in identifying regional metastases, and alternating them over time could allow to reduce the number of follow-up visits. CT scans, differently from chest x-ray, showed a high power in identifying distant metastases. Surveillance follow-up schedules in the literature vary significantly depending on country, physician specialty, and stage of disease, with a lack of evidence on the efficacy of the different schemes. Standard protocols are desirable for a better evaluation of results. Highlights: Guidelines for melanoma follow-up differ in timing, duration and methods across countries. Physical examination and ultrasounds are equally powerful in the identification of regional metastases. Recommendations on imaging tests or blood tests are different and often based on low levels of evidence. Standardization of protocols would be desirable to ensure better evaluation of results.